Study on the Formation of Proplastids in Apical Meristem of Wheat - Semenova, Galina A. (Research Highlights in Agricultural Sciences Vol. 1, 2022)
In this work, the images of the formation of proplastids of the apical meristem of wheat seedlings were obtained and described for the first time in the scientific literature. Proplastids—precursors of chloroplasts—are found in the apical meristem of the growth point of plants. Researchers focused their attention primarily on how proplastids become chloroplasts. In the current work, the apical meristem of wheat seedlings' proplastid production was examined and reported for the first time in the scientific literature. Ultrastructural images of apical meristem areas showed that the formation of the proplastide body includes several stages: localization of plastid DNA in the cytoplasmic matrix in close contact with cytoplasmic ribosomes, the formation of membrane vesicles containing plastid DNA, the step-by-step filling of these vesicles with dense contents, and the formation of mature proplastids.